Asymptomatic cholecystitis and its controversial issues in biliary surgery - Sergey Yurievich Muraviev; Evgeniy Alexandrovich Tarabrin; Alexey Leonidovich Shestakov; Irina Alexandrovna Tarasova; Ivan Alexandrovich Markov; Vadim Sergeevich Razumovsky; Anna Victorovna Ananichuk; Andrey Pavlovich Fabrika; Valeria Alexandrovna Stener; Mehrshad Ebrahimnezhad; Denis Vasilievich Orlushin; Anna Nikolaevna Zavyalova (Asian Journal of Surgery)
Gallbladder stones are present in 10–20 % of the population of Western countries, and the incidence rate has almost tripled over the past 30 years. Asymptomatic cholecystitis is more common than it is mentioned in the literature. Approximately 80 % of the GI have no clinical manifestations. In most cases, the disease will remain asymptomatic throughout life.The problem of asymptomatic cholecystitis is often hushed up and ignored. Surgeons try to avoid examining this pathology. Works on asymptomatic cholecystitis are not only few, but also scattered. At the same time, there is no uniformity in the literature. Since the tactics of treating such patients still does not have an unambiguous approach. Many surgeons doubt the decision on surgical treatment, a smaller part chooses cholecystectomy at the same time, without substantiating the indications for it. That is why most cases of postcholecystectomy syndrome occur in patients operated on for asymptomatic cholecystitis.The unwillingness to discover the secret of stone formation and asymptomatic cholecystitis in humans when concretions in the gallbladder are detected without reference to surgery, to indicate the trajectory of the examination, leads to a number of tactical errors, preserving the risk of PES, and erasing practical recommendations for the management of such patients. The solution to this issue lies in a thorough study of each stage of the tactical search in patients with asymptomatic cholecystitis, which will determine a new strategy in biliary surgery.